Fatores clínico-radiográficos e da formação profissional associados à tomada de decisão em endodontia - Peserico, Luahra (2023)
The present “before and after” study aimed to evaluate the association of clinical/radiographic and professional qualification factors with clinical decision making regarding the management of root-canal treated teeth. It also investigated whether clinical information changes the treatment options of students and professionals in relation to isolated radiographic analysis. Electronic questionnaires were sent to 56 participants with different levels of professional qualification: undergraduate students, general practitioners, endodontics postgraduate students and endodontists. Thirty clinical cases were evaluated at two different moments. In the first questionnaire (Q1), periapical radiographs were provided. After one month, a second questionnaire (Q2) was answered, additionally containing clinical information. In both moments, participants chose the best treatment option for each case: wait-and-see, nonsurgical retreatment, apical surgery, nonsurgical retreatment + apical surgery or extraction. Changes in treatment options from Q1 to Q2 were analysed by the McNemar test. Multilevel binary logistic regression models were used to assess the association of examiner-related and clinical case-related factors with decision making (wait-and-see or reintervention) (α=0,05). Participants were more likely to indicate the wait-and-see and nonsurgical retreatment options at both moments. Endodontists more frequently recommended reintervention in Q2 compared to Q1. In Q1, the following variables were significantly associated with the decision to indicate a tooth to reintervention: examiner’s age, dental group, iatrogenic errors, root filling quality, periapical status and quality of coronal restoration/prosthetic crown. In Q2, specialty training in endodontics and the treatment option in Q1 were significantly associated with reintervention. Furthermore, the outcome was associated with the variables dental arch, post and/or prosthetic crown, time since the end of endodontic treatment (ET), iatrogenic errors, signs and/or symptoms and root filling quality. In conclusion, conservative approaches were preferred by all participants. Endodontists more frequently chose reintervention in Q2 than in Q1. In both questionnaires, the presence of iatrogenic errors and root filling quality were associated with reintervention. Additional variables in Q1 (examiner’s age, dental group, periapical status and quality of coronal restoration/prosthetic crown) and Q2 (specialty training in endodontics, treatment option in Q1, dental arch, post and/or prosthetic crown, time since the end of ET and signs and/or symptoms) were also associated with the outcome.